Hubungan Kepatuhan Masyarakat dalam Melakukan Protokol Kesehatan dengan Kesiapan Beradaptasi Covid-19 - Fatimah Az-Zahra; Desmawati Desmawati (Master of Epidemiology, School of Postgraduate Studies, Diponegoro University, Indonesia, 2023)
Background: Pandemic of the Covid-19 needs serious attention. This is because the rate of spread of this virus is very fast, so that an attitude and the understanding of obedience to health protocol is needed to stop the spread of the Covid-19. This study aims to find the relationship between community obedience in carrying out the health protocols and the readiness to adapt with Covid-19.Methods: This study used quantitative research with a cross sectional, which was conducted in one of Rukun Warga in Pamulang district with a sample of 231 people who were selected according to the inclusion criteria from total positive Covid-19. Collecting data using a questionnaire that has been tested for validity and reliability with Crobach's value of 0.899 > 0.361. The statistical test used univariate analysis using descriptive statistics and bivariate analysis using Chi-square test.Result: The results of this study were reported that there was relationship between Community Obedience in carrying out the health protocols with the readiness to adapt toward Covid-19.Conclusion : The conclusion, community obedience in carrying out the health protocols have significant relationship in order to be ready and adaptation to Covid-19.